King, Charleigh. The Poltergeist. - Jarvis, Dale Gilbert, 1971- (2011)
Recording of a ghost story told by Charleigh King, a Grade 7 student at I.J.Sampson school. Recorded in the Newman Wine Vaults Provincial Historic Site as part of the Young Folklorists Program run by the Heritage Foundation of Newfoundland and Labrador in May, 2011. Charleigh writes, "My story takes place in an old house on my friend's birthday. We heard crashing glasses in the kitchen, but when we looked out, there was nobody, just crashed glass. The house was said to be haunted."